Outbreak of Burkholderia cepacia pseudobacteraemia caused by intrinsically contaminated commercial 0.5% chlorhexidine solution in neonatal intensive care units. Issue 3 (March 2018) - Song, J.E.; Kwak, Y.G.; Um, T.H.; Cho, C.R.; Kim, S.; Park, I.S.; Hwang, J.H.; Kim, N.; Oh, G-B.
Summary: Background: Burkholderia cepacia is intrinsically resistant to certain antiseptics. The authors noted a sudden increase in the frequency of isolation of B. cepacia from blood cultures in a neonatal intensive care unit (NICU) of a university-affiliated hospital. Aim: To identify the source and intervene in the ongoing infections. Methods: The cases were defined as patients with positive blood cultures for B. cepacia in an NICU between November 2014 and January 2015. Medical records were reviewed and NICU healthcare workers were interviewed. Samples of suspected antiseptics, blood culture bottles, cotton balls, gauze and a needle used in the NICU were analysed microbiologically. Findings: During the outbreak period, B. cepacia was identified in 25 blood cultures obtained from 21 patients. The clinical features of the patients were suggestive of pseudobacteraemia. Regarding environmental samples, B. cepacia was cultured from 0.5% chlorhexidine gluconate (CHG) solution products that had been used as a skin antiseptic during blood drawing in the NICU. The clinical B. cepacia isolate and two strains obtained from 0.5% CHG exhibited identical pulsed-field gel electrophoresis patterns. After the CHG products were withdrawn, the outbreak was resolved. Conclusions: The pseudobacteraemia cases were caused by contaminated 0.5% CHG produced by a single manufacturer. Stricter government regulation is needed to prevent contamination of disinfectants during manufacturing. In addition, microbial contamination of antiseptics and disinfectants should be suspected when a B. cepacia outbreak occurs in hospitalized patients.